Pengaruh Jasa Angkutan Umum Terhadap Penyerapan Tenaga Kerja di Kabupaten Pinrang - Asrianti A; Herniah S; Asdinar Wahid Awaluddin (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of public transportation services on employment in Pinrang Regency in 2020-2022. Techniques used in data collection include: Observation, Interview, Documentation. The data analysis method used is Simple Regression analysis. The results of this study indicate that there is an effect of public transportation services on employment in Pinrang Regency in 2020-2022.